Efficacy of the herb, withania somnifera l. In the prevention of stress-induced alterations in the ovary of rat - DIVYASHREE S; YAJURVEDI HN (International Journal of Pharma and Bio Sciences, 2017)
The present study aims to investigate the efficacy of the herb ashwagandha in the prevention of stress-induced alterations in the ovary. Exposure of rats to two stressors i.e. restraint (1 h), then after a gap of 4 h to forced swimming exercise (15 minutes) every day for 4 weeks resulted in a significant increase in the adrenocortical activity, indicating the activation of hypothalamo-pituitary-adrenal axis. Concomitantly, there was a decrease in the weight, activities of 3β-hydroxysteroid dehydrogenase and antioxidant enzymes, number of healthy antral follicles, corpora lutea and percentage of healthy granulosa cells of the ovary, whereas the number of atretic follicles, the percentage of apoptotic granulosa cells and malondialdehyde concentration of the ovary showed an increase in the stressed rats compared to those of controls. However, stressed rats pre-treated with the alcoholic extract of ashwagandha (10mg/ kg body weight, oral) did not show these adrenal and ovarian stress responses and did resemble controls. The results for the first time reveal that an extract of ashwagandha is potent enough to inhibit activation of hypothalamo-pituitary-adrenal axis and maintain normal gametogenic and antioxidant activities of the ovary under stressful conditions.